Marketing Communication Discas Mobile Apps - Reni Sara Indrawati; Irwansyah Irwansyah (International Journal Labs, 2023)
Communication, Technology, and Society have an effective role in building globalization. Marketing communications, emerging technologies, and intelligent societies present in globalization are making many impacts on the life of the world. Digital technology is able to make it easy for people to find information, find groups and provide responses widely and freely. A digital app on mobile called DisCas tries to differentiate it from other social pedia digital technologies. DisCas a start is growing for a noble cause. Starting from unrest in society when a problem arises, many opinions and misinformation are scattered and do not solve the problem. DisCas is here to fulfill an application called Social Pedia, a responsible opinion and provide appreciation in the form of buying and selling opinions, ideas, captions, images, photos, and videos. The research method uses interview techniques with CEH DisCas interviewees. The results of the discussion of marketing communications presented by DisCas rely on digital marketing, advertising in print and digital media, creative content through endorsers, and even asking me anything or AMA in a conversation about blockchain. The conclusion of this article states that Social Pedia has a good future and extraordinary achievement of social pedia that is packaged responsibly and easily benefits through image ideas, opinions, and works easily accessible to all levels of society in the world using mobile application technology.